White Australia policy - Wellington, Jo; Garner, Simon; Classroom Video (Australia : Classroom Video, 2009)
This program examines a longstanding series of Australian government immigration policies that, from Federation up until the mid-1970s, favoured white, English-speaking and culturally similar people
Title from container
Executive producer, Garner, Simon
DVD Format
Keywords: White Australia policy; Aboriginal Australians -- Government relations; Aboriginal Australians -- History; Racism -- Australia -- History; Immigrants -- Government policy -- Australia -- History